COMMUNICATION STRATEGIES USED BY UNIVERSITY LEARNERS IN SPEAKING FOR DISCUSSION CLASS OF ENGLISH DEPARTMENT SURABAYA STATE UNIVERSITY (RETAIN, 2015)
Abstrak Penelitian ini mendiskripsikan penggunaan communication strategies di speaking for discussion class di jurusan pendidikan bahasa inggris Universitas Negeri Surabaya. Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan communication strategies oleh mahasiswa dalam kelas diskusi dan kemampuan speaking mereka menggunakan strategi tersebut. Penelitian ini menggunakan metode deskriptif kualitatif, meneliti penggunaan Communication Strategies dalam kelas speaking for discussion. Catatan saat di lapangan, wawancara, dan hasil diskusi mahasiswa digunakan untuk mengumpulkan data dalam penelitian ini. Subjek penelitian ini adalan kelas speaking for discussion E di jurusan pendidikan bahasa inggris yang ditempuh mahasisiwa semester tiga. Hasil penelitan menunjukkan bahwa: Pertama, ada sembilan communication strategi dari teori Dornyei (1995) yang digunakan mahasiswa untuk menyampaikan ide dalam kelas diskusi antara lain; message abandonment, approximation, stalling, literal translation, code switching, appeal for help, cicumlocution, use all-purpose word, dan mime. Mahasiswa menggunakan strategi message abandonment saat mereka menghapi kesulitan pada topik yang sedang mereka diskusikan. Approximation, literal translation, circumlocution, dan mime digunakan mahasiswa untuk menyampaikan ide dalam diskusi dengan mendeskripsikan objek atau istilah dalam bahasa inggris dengan bahasa mereka sendiri. Stalling digunakan oleh mahasiswa untuk mengingat materi apa yang akan mereka sampaikan dalam diskusi. Appeal for help digunakan dengan bertanya langsung pada guru atau teman dalam diskusi. Code switching dan use all-purpose word digunakan dengan langsung mengucapkan bahasa Indonesia saat diskusi. Kedua, penelitian ini menunjukkna bahwa mahasiswa yang menggunakan strategi message abandonment dan code switching tidak memberikan argumen yang jelas dalam diskusi dan terlalu banyak menggunakan bahasa Indonesia sehingga mereka tidak memnuhi kriteria berbicara menurut Morreale dkk (2007). Namun sebaliknya, mahasiswa yang menggunakan strategi approximation, stalling, literal translation, circumlocution, appeal for help, dan mime mereaka lebih mandiri dalam menyampaiakan ide mereka dalam diskusi menggunakan bahasa mereka sendiri yang mengindikasikan mereka telah memenuhi kriteria berbicara dalam kelas diskusi. Kata Kunci: Speaking, Learning Strategy, Communication Strategies, Speaking for Discussion. Abstract This study investigated the use of communication strategies in Speaking for Discussion Class of English Department Surabaya State University. This study was aimed to describe how the university learners used communication strategies in their speaking discussion activity and the result of the learners’ speaking ability through their performance using communication strategies. This study was descriptive qualitative research, observing the use of communication strategies in speaking for discussion. Field notes, interview, and learners’ speaking for discussion performance result were used as the instruments to collect the data. The learners of speaking for discussion E class majoring English Education in third semester of Surabaya State University were chosen as the subject of this study. The consideration was based on the learners’ speaking performance. The result of this study showed that: First, there were nine communication strategies proposed by Dornyei (1995) which were used by the learners in speaking for discussion. The learners used message abandonment strategy by giving up on a topic because it was too difficult and they did not give more explanation toward the topic they were discussing. Approximation, literal translation, circumlocution, and mime were used by the learners by describing an object or event instead of using an appropriate vocabulary item and gesture or other nonverbal mean refers to an object or event. Stalling or time-gaining strategy was used by the learners by employing fillers or hesitation device to fill pauses and to gain time to think the ideas they were going to express. Appeal for help was used by the learners by asking their friends or lecturer in the middle of their speaking. Code switching and use all-purpose word were used by the learners to express their ideas by employing L1 and using unessential word in their speaking. Second, this present study found that when the learners used message abandonment, use all-purpose-word, and code switching strategy, they didn’t give more explanation about their supporting arguments and employed a lot of L1 in their speaking which meant they hadn’t accomplished the criterions of speaking performance. Meanwhile, the other strategies such as approximation, literal translation, stalling, circumlocution, appeal for help, and mime brought about the learners were more independent to express their ideas and deeply thinking when they found some difficult or unfamiliar terms in L2 which meant they had accomplished the criterions of speaking performance. Key Words: Speaking, Learning Strategy, Communication Strategies, Speaking for Discussion.